Self sufficient urban architecture: reducing reliance on traditional sources for basic necessities - Sineke, Lundi (School of Architecture, Planning and Geomatics, 2025)
With the growing popularity of sustainable and self-sufficient living, architects and urban planners have discovered numerous examples of such communities located outside urban areas. However, the principles of sustainable living can also be effectively applied within urban environments. The objective of this project is to explore the design principles and practices of off-the-grid, self-sufficient architecture, and assess its potential in creating more sustainable and self-reliant urban developments in cities or urban areas. My grandmother, who has been residing on an off-the-grid self-sustaining farm for several decades, sparked my curiosity in investigating self-sufficiency. I firmly believe that the farm's design principles can serve as a solid foundation for architects and urban designers to create more self-sufficient urban developments. Despite the farm's simplicity, it embodies various sustainable design principles that can be seamlessly integrated into urban projects. One remarkable feature demonstrated by the farm is its water conservation practices. Through the implementation of a simple water recycling system, the farm eliminates its dependence on municipal water sources. This noteworthy achievement inspires the incorporation of water-efficient fixtures in building designs. By including rainwater harvesting and grey water recycling systems in architectural plans, reliance on conventional water sources can be further reduced, encouraging a more sustainable and responsible use of water resources. The farm's agricultural aspect presents an opportunity to redefine the relationship between buildings and their surrounding environments. By embracing the concept of urban agriculture, designs can be crafted to encompass community gardens and green spaces, fostering a sense of shared ownership and sustainable food production within urban settings. Furthermore, the integration of rooftop gardens into building designs not only optimises land utilisation but also nurtures a harmonious synergy between nature and architecture. This approach simultaneously improves air quality, mitigates the urban heat island effect, and enhances overall urban aesthetics. Ultimately, the farm's integration of sustainable design principles serves as an influential source of inspiration, providing a blueprint for creating environmentally conscious and socially responsible built environments. By thoughtfully incorporating these principles into designs, professionals can drive positive change by reducing energy consumption, conserving water resources, promoting self-sufficiency through urban agriculture, and mitigating the environmental impact of buildings. Embracing such practices will undoubtedly contribute to a more sustainable future, enhancing the overall quality of life within our urban communities and fostering a harmonious coexistence between human activities and the natural world.